Analisis Pengelolaan Sumber Daya Air Oleh BUMN, BUMD dan BUMS Sebagai Bentuk Kerjasama Dalam Meningkatkan Perekonomian Nasional - Iksanudin Nursantosa; Tumpal Paskalis; Muhammad Hariyadi; Muhamad Ramhadan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The basic need of society is water and how water is managed has a great impact on social activities. The government of Indonesia has the right and power to administer and make use of water resources in accordance with Law No. 17 of 2019 and Article 33 Paragraph 3 of the 1945 Constitution. In terms of regulation, the government is crucial the best way to use water to suit societal demands. Although SOEs and BUMDs are responsible for water resources to be managed for the benefit of society, they still face obstacles and require assistance from BUMS or the private sector. Political and regulatory changes in Indonesia also affect the process of managing water resources, including the repeal of relevant laws that may impact projects already underway. Companies can only manage water resources if all community demands are met and they comply with standards set by the Constitutional Court. The interests of the community must come first in managing water resources that used effectively for the community.